2021
DOI: 10.21203/rs.3.rs-298978/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes of the Blood Lymphocytes On Severe Trauma Patients in Early Time

Abstract: Purpose: To evaluate the relationship between the change of blood lymphocyte counts in early stages of trauma patients and the secondary tissue injury after trauma. Method: A retrospective study was conduct to include trauma patients with Injury Severity Score(ISS) ≥16 between January 1 st , 2018 and December 31 st , 2019. Lymphocyte counts of each trauma patient were collected and recorded in first 3 hours, 6-12 hours, 24-48 hours, and 49-72 hours after trauma, separately. The degree of secondary on the traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has been shown that lymphocyte counts decrease immediately after trauma in patients compared to the control group (167,209), although significant decreases in the number of lymphocytes between MOF and non-MOF groups appear after day 2 (169). Accordingly, lymphopenia is detectable during days 2 to 7 after trauma in the MOF group.…”
Section: Adaptive Immune Cellsmentioning
confidence: 95%
“…It has been shown that lymphocyte counts decrease immediately after trauma in patients compared to the control group (167,209), although significant decreases in the number of lymphocytes between MOF and non-MOF groups appear after day 2 (169). Accordingly, lymphopenia is detectable during days 2 to 7 after trauma in the MOF group.…”
Section: Adaptive Immune Cellsmentioning
confidence: 95%